Ljudske pravljice v osnovni šoli - Haramija, Dragica (Jezik in slovstvo, 2019)
The paper presents folk fairy tales, focusing on the theoretical starting points of this literary form (structure, basic motivic-thematic elements), while also considering the operational goals of the school national curriculum for Slovenian (Učni načrt Slovenščina, 2018). From the point of view of (children's) literary studies, the elements of the fairy tale that pupils should be able recognise by the end of the second educational cycle are presented in greater detail: literary persons (real, fairytale); literary time and space (indefinite time and space, as they are mentioned only indirectly in fairy tales); commandments, prohibitions and prophecies (as tests); magical events (in magical fairy tales); and typical structure (usually with a happy ending). These elements (UNS 2018) are mostly illustrated with examples from Slovenian folk fairy tales, which are an important part of the national cultural heritage.
Keywords: curriculum; elementi pravljice; ljudske pravljice; osnovna šola; učni načrt